Student wellbeing during COVID-19—Impact of individual characteristics, learning behavior, teaching quality, school system-related aspects and home learning environment - Brauchle, Julian; Unger, Valentin; Hochweber, Jan (Frontiers in Education, 2025)
IntroductionThe measures taken to contain the COVID-19 pandemic had a significant impact on the lives of young people. Studies indicate a decrease in wellbeing and an increase in mental health problems among adolescents. However, the influence of individual or contextual factors on student wellbeing has hardly been investigated to date.MethodsIn the present study, we used a cross-sectional survey design to examine the impact of individual student characteristics and learning behavior, teaching quality, school system-related aspects and home learning environment on the wellbeing of N = 1,212 secondary school students from Germany and Switzerland (grade level: 5–13; age: 10–20) during the pandemic. Most students completed the survey retrospectively, while some students were in quarantine at the time of the survey.ResultsIn stepwise multivariate regression models, higher student socioeconomic status and perceived teacher support were found to be positive predictors of wellbeing, while more frequent procrastination was found to be a negative predictor. Lower levels of wellbeing were found for female and older students, and German (compared to Swiss) students.DiscussionOur study contributes to the assessment of the impact of the COVID-19 pandemic on student wellbeing, specifically to the identification of particularly affected or vulnerable groups. This may help to better prepare education systems for future, comparable situations and to mitigate negative outcomes for students.